Program Pendampingan Komprehensif untuk UMKM Kota Bandar Lampung: Legalitas Usaha dan Literasi Keuangan Syariah - Mirza. BR, Aryan Danil; Putra, Joni; Desriani, Neny; Rohman, Fatkhur (Penerbit Goodwood, 2024)
Purpose: Using the Online Single Submission (OSS) platform (oss.go.id), this mentoring initiative seeks to assist Medium and Small Enterprise (MSME) partners in achieving company legality. The service staff also provides thorough sharia financial training in an effort to inculcate Islamic ideals. This entails improving knowledge of sharia principles, raising awareness of Islamic financial products that are accessible, and making it easier to access finance options for businesses. Methodology: The program takes a multifaceted approach that incorporates discussions, lectures, and practical experience. This approach guarantees that participants may immediately apply the knowledge to their company operations in addition to comprehending the theoretical components. Results: The program has demontrate that MSMEs can better position themselves to obtain finance from a variety of sources and are more capable of attaining sustainable development. These include of government grants and funding initiatives like Islamic banks' Kredit Usaha Rakyat (KUR). Additionally, having a legal corporate standing gives access to larger markets, such as contemporary commerce and export prospects. Limitations: MSMEs in Bandar Lampung City are the focus of this mentoring program because of their need for business legality and comparatively high degree of technology awareness. Contribution: This activity provides significant added value by addressing critical challenges faced by MSMEs, particularly in navigating the legal and financial aspects of business operations. By equipping participants with practical skills and knowledge, the program enhances their ability to compete in increasingly competitive markets.